Frequency and abundance of Sparganium erectum L. and Trapa natans L. (macrophytes) altered by bird foraging in Hokersar wetland, Kashmir - Suzana Bashir, Azra N Kamili, Manzoor A Shah and Humera Imtiyaz (International Journal of Advanced Science and Technology, 2020)
Hokersar wetland in Kashmir, Himalaya hosts a large number over-wintering  waterbirds as well as summer migratory and resident birds. All these birds largely depend on the macrophytes growing in the wetlands for nest building, for cover during breeding,  moulting,  preening and for food. High concentrations of waterbirds in wetlands are known to affect ecosystem dynamics, yet very few studies have examined their effects on the dynamics of macrophytes. In the present study two aquatic macrophytes, Sparganium erectum L  and Trapa natans L  typical of wetlands and eutrophic lakes, were taken into consideration  for their use by the birds inhabiting the wetland.  Sparganium erectum is found growing in shallower waters while as  Trapa natans  thrived well in open deeper waters. Water birds were observed to depend on leaves, roots and seeds of the two plants and had an impact on the population dynamics of these plants. It was also observed that nutrient loading resulted in gregarious growth of these macrophytes and in turn waterbirds  reduced the biomass and also reshaped  the vegetation composition of the wetland. Our data support the view that waterbirds may paly crucial role in the sustenance of certain plant species  with potential consequences for the functioning of the system as a whole. The fact that bird herbivory can have a large impact on macrophyte biomass and can facilitate a regime shift, so it is implied that the presence of waterfowl should be taken into account in the estimation of critical loadings to be used in water quality management.